DUQuE quality management measures: associations between quality management at hospital and pathway levels - WAGNER, CORDULA; GROENE, OLIVER; THOMPSON, CAROLINE A.; DERSARKISSIAN, MARAL; KLAZINGA, NIEK S.; ARAH, ONYEBUCHI A.; SUÑOL, ROSA (International journal for quality in health care, 2014)
Objective. The assessment of integral quality management (QM) in a hospital requires measurement and monitoring from different perspectives and at various levels of care delivery. Within the DUQuE project (Deepening our Understanding of Quality improvement in Europe), seven measures for QM were developed. This study investigates the relationships between the various quality measures. Design. It is a multi-level, cross-sectional, mixed-method study. Setting and Participants. As part of the DUQuE project, we invited a random sample of 74 hospitals in 7 countries. The quality managers of these hospitals were the main respondents. Furthermore, data of site visits of external surveyors assessing the participating hospitals were used. Main Outcome Measures. Three measures of QM at hospitals level focusing on integral systems (QMSI), compliance with the Plan-Do-Study-Act quality improvement cycle (QMCI) and implementation of clinical quality (CQII). Four measures of QM activities at care pathway level focusing on Specialized expertise and responsibility (SER), Evidence-based organization of pathways (EBOP), Patient safety strategies (PSS) and Clinical review (CR). Results. Positive significant associations were found between the three hospitals level QM measures. Results of the relationships between levels were mixed and showed most associations between QMCI and department-level QM measures for all four types of departments. QMSI was associated with PSS in all types of departments. Conclusion. By using the seven measures of QM, it is possible to get a more comprehensive picture of the maturity of QM in hospitals, with regard to the different levels and across various types of hospital departments.